Lecture type discourse: its make-up in terms of inter-sentence connectives and discourse markers. - Basil S. Wijasuria. (Universiti Kebangsaan Malaysia, 1974)
This paper is an analysis of lecture-type discourse in terms of inter-sentence connectives and discourse markers. This study has been prompted by the fact that many non-native speakers of English at university level in countries where the medium of instruction is English, have listening comprehension difficulties in lecture situations. These difficulties arise even when the student concerned has paper qualifications of a high order. This paper analyzes a sample of lecture material over a wide range of subjects, such material being recorded in actual lecture situations, and the data obtained is classified and presented together with occurance counts of each item. The paper then goes on to discuss the implications of inter-sentence connectives and discourse markers to listening comprehension and to suggest that these items might be the key to facilitating listening comprehension.